2017
DOI: 10.1002/cncr.31140
|View full text |Cite
|
Sign up to set email alerts
|

Prostate cancer screening with prostate‐specific antigen: Where are we going?

Abstract: Current prostate‐specific antigen screening is not cost‐effective from a public health perspective. A new algorithm using genetic testing and imaging has yet to be developed. See also pages 507‐13.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…A reliable predictive maker of radiosensitivity can effectively guide personalized treatment decisions. Currently, glycosylated proteins have become one of the most common cancer biomarkers in the clinic, such as alpha-fetoprotein (AFP) for hepatocellular carcinoma [67], carcinoembryonic antigen (CEA) for colon cancer [68] and prostate specific antigen (PSA) for prostate cancer [69]. However, glycoprotein-related predictive maker for breast cancer, especially for radioresistant breast cancer, remains blank.…”
Section: Discussionmentioning
confidence: 99%
“…A reliable predictive maker of radiosensitivity can effectively guide personalized treatment decisions. Currently, glycosylated proteins have become one of the most common cancer biomarkers in the clinic, such as alpha-fetoprotein (AFP) for hepatocellular carcinoma [67], carcinoembryonic antigen (CEA) for colon cancer [68] and prostate specific antigen (PSA) for prostate cancer [69]. However, glycoprotein-related predictive maker for breast cancer, especially for radioresistant breast cancer, remains blank.…”
Section: Discussionmentioning
confidence: 99%
“…This is not without controversies. Most PSA—identified PCa are localized and usually low-grade disease, many of which never progress or become clinically relevant only after ~20 years [ 7 ]. This in itself raises the question of overdiagnosis of low-grade PCa, especially as the rapidly growing, difficult-to-treat, high-grade PCa are seldom found by PSA testing [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most PSA—identified PCa are localized and usually low-grade disease, many of which never progress or become clinically relevant only after ~20 years [ 7 ]. This in itself raises the question of overdiagnosis of low-grade PCa, especially as the rapidly growing, difficult-to-treat, high-grade PCa are seldom found by PSA testing [ 7 , 8 ]. More so, being a highly sensitive biomarker, an abundance of false positives cannot be ruled out, and this is further compounded by the lack of consensual cut-off to delineate indolent from clinically relevant disease, thus yielding a pool of false positives and negatives [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, some study has shown that only 32.4% of patients with a PSA 4.0 ng/mL or higher had PCa [2]. Thus, current PSA screening is not cost-effective from a public health perspective [3] and many urologists are concerning for over-diagnosis of PCa with widespread serum PSA screening, which eventually could lead to overtreatment of PCa and its accompanied morbidities. And also, prostate biopsy under transrectal ultrasound (TRUS) is the only tool for diagnosing PCa, but it is invasive and can cause side effects such as infection and gross hematuria, and can give considerable discomfort to the patients during procedure.…”
Section: Introductionmentioning
confidence: 99%